Consolidating Regional Integration Through a Free Movement Protocol: The Quest for Collective Development in the SADC - VICTOR H MLAMBO (African Journal of Governance and Development, 2020)
This paper examines whether a free movement protocol in the Southern African Development Community (SADC) would deepen and consolidate regional integration and development. Political discourse in the SADC has argued for the need to consolidate collective development considering the changing trajectory of the socio-economic conditions in the region. An examination of regional integration literature reveals that: the lack of political will, borders and their colonialist legacies and the competing interests of states are challenges stifling regional integration in the SADC region. Regardless of the associated economic benefits, a free movement protocol would not change the economic trajectory of the region until such challenges are addressed. Moving beyond these challenges, the capacitation of regional institutions and establishing inter-state ministerial committees to study the impact of a free movement protocol in the SADC would be the first step in consolidating regional integration.